Students' Knowledge and Perceptions of Heroic Values in History Education: A Case Study of Mohamad Hatta in Post-Colonial Indonesia - Syaiful Ma'ruf; Suwito Eko Pramono; Syaiful Amin (Indonesian Journal of History Education, 2026)
Abstract: This study critically examines students' knowledge and perceptions of the heroic values embodied by Mohamad Hatta, Indonesia's first Vice President and a key figure in the Proclamation of Independence. Drawing on quantitative survey data from 34 students at SMA Negeri 1 Candiroto, the research investigates two dimensions: factual knowledge of Hatta's biography and roles, and perceptions of his heroic values including courage, responsibility, discipline, sacrifice, patriotism, mutual assistance, and perseverance. The findings reveal high levels of both knowledge (84.7%) and perception (88.14%), suggesting effective transmission of nationalist narratives. However, this study argues that high scores on declarative knowledge and value affirmation do not necessarily indicate deep historical understanding or internalised commitment. The research contributes to broader international conversations about how post-colonial societies construct and transmit heroic narratives through history education, and the tensions between knowledge transmission and critical historical consciousness development.   Abstrak: Studi ini mengkaji pengetahuan dan persepsi siswa mengenai nilai-nilai kepahlawanan Mohamad Hatta, Wakil Presiden pertama Indonesia dan tokoh kunci Proklamasi. Berdasarkan survei kuantitatif terhadap 34 siswa di SMA Negeri 1 Candiroto, penelitian menyelidiki dua dimensi, yaitu pengetahuan faktual tentang biografi Hatta dan persepsi terhadap nilai kepahlawanan seperti keberanian, tanggung jawab, disiplin, pengorbanan, patriotisme, gotong royong, dan ketekunan. Temuan menunjukkan tingkat pengetahuan tinggi (84,7%) dan persepsi (88,14%), mengindikasikan transmisi narasi nasionalis yang efektif. Namun, studi berargumen bahwa skor tinggi pada pengetahuan deklaratif tidak otomatis menunjukkan pemahaman historis mendalam atau komitmen terinternalisasi. Penelitian ini berkontribusi pada diskusi tentang bagaimana masyarakat pascakolonial mengonstruksi dan mentransmisikan narasi kepahlawanan melalui pendidikan sejarah.